Risk Factors Associated With Driving After Cannabis Use Among Canadian Young Adults. (April 2022) - Huỳnh, Christophe; Beaulieu-Thibodeau, Alexis; Fallu, Jean-Sébastien; Bergeron, Jacques; Flores-Aranda, Jorge; Jacques, Alain; Brochu, Serge
This study identifid the most prominent risk factors associated with driving after cannabis use (DACU). 1, 126 Canadian drivers (17–35 years old) who have used cannabis in the past 12 months completed an online questionnaire about sociodemographic information, substance use habits, cannabis effect expectancies, driving behaviours and peers' behaviours and attitudes concerning DACU. A hierarchical logistic regression allowed identifying variables that were associated with DACU. Income (CA30, 000–CA69, 000), weekly-to-daily cannabis use, higher level of cannabis-related problems, expectation that cannabis facilitates social interactions, drunk driving, belief that DACU is safe, general risky driving behaviours, having a few friends who had DACU and injunctive norms predicted past 12-month DACU. Older age, holding negative expectations concerning cannabis, driving aggressively and perceived accessibility of public transportation decreased the probability of DACU. With restricted resources, programmes will be more efficient by targeting Canadian young adults most inclined to DACU by focussing on these risk factors.